the Level of Knowledge of Third Trimester Pregnant Women About Birthing Ball Therapy To Reduce Pain During Childbirth at Helen Tarigan Clinic in 2022 - Aprilita Sitepu; Yuni Manurung (Institute of Computer Science (IOCS), 2022)
Pregnancy is defined as fertilization or fusion of spermatozoa and ovum and subsequent implantation. The third trimester of pregnancy is often called a period of waiting and full of vigilance. Some fears arise in the third trimester. Birthing ball is one of the gymnastic techniques as well as therapy for physical training for all pregnant women and is able to help improve comfort and fitness for pregnant women. Based on research in May at Helen Tarigan Clinic, it was found that most mothers did not know for sure about the benefits of Birthing Ball therapy to reduce pain during labor. The sampling technique is accidental sampling. The location of this research was at Helen Tarigan Clinic 2022, May 2022. With 26 respondents, the measuring instrument used is a closed questionnaire, which is tested for validity with a frequency distribution. The results showed that of the 26 respondents at Helen Tarigan Clinic, there were respondents who had sufficient knowledge. Based on respondents who have sufficient knowledge as many as 18 people (69%), based on age with sufficient knowledge as many as 18 people (69%), based on education with sufficient knowledge as many as 3 people (75%), based on occupations with sufficient knowledge as many as 6 people (100% ) and based on parity with sufficient knowledge as many as 3 people (100%). In conclusion, it is hoped that pregnant women will seek the latest information about a unique way to reduce pain during labor, what is a birthing ball and the benefits of childbirth.